Implementation of a sensory modulation intervention in mental health outpatient services: a process evaluation study - Klara Forsberg; Daniel Sutton; Sigrid Stjernswärd; Ulrika Bejerholm; Elisabeth Argentzell (BMC Psychiatry)
Abstract Background Mental health service users often experience difficulties interpreting and regulating sensory stimuli resulting in increased anxiety, decreased abilities to engage in activities and a hampered recovery process. However, there are limited studies on the implementation of such recovery-oriented interventions targeting sensory difficulties via sensory modulation techniques. Therefore, the aim of this study was to investigate staff and manager views on the implementation process of a group-based sensory modulation intervention in mental health outpatient services in Southern Sweden. Methods This mixed method implementation process evaluation included eight outpatient units, which were also study sites for a Randomized Controlled Trial (RCT) (NCT06432114), evaluating the effectiveness of the sensory modulation intervention. Quantitative data were analysed using descriptive statistics and qualitative data were analysed using deductive and inductive content analysis. Results The results indicated that the intervention was highly accepted by the mental health staff. The dose delivered and received were high and the intervention in general met the needs of the target group. Managers and staff reflections indicated that following the intervention service users seemed to feel better prepared to handle anxiety in daily life due to the acquisition of new sensory coping strategies. Staff expressed that they benefitted from acquiring a different perspective or “new sensory glasses” to apply in their clinical practice. However, managers’ and staff reflections also highlighted the need for an adapted manual for people with cognitive issues and more education for staff. Conclusions This study contributed to new knowledge of implementing a recovery-oriented sensory modulation intervention in mental health outpatient services. The implementation was generally carried out as intended. Nonetheless, certain challenges emerged during the implementation process, both within the contextual environment and during the delivery of the intervention. Trial registration Retrospectively registered 20,240,529, in ClinicalTrials.gov NCT06432114.